2017
DOI: 10.19044/esj.2017.v13n24p483
|View full text |Cite
|
Sign up to set email alerts
|

Activite Antifongique Des Extraits Aqueux De Calendula Officinalis L, Urginea Maritima (L.) Baker Et Chenopodium Ambrosioides L.

Abstract: Fungi are the cause of many human, animal and plant diseases. In the context of valorization of aromatic and medicinal plants of the Central Middle Atlas of Morocco, three plants were selected, based on the results of an ethnobotanical survey in this region, to evaluate their antifungal activity against five Fungi, namely Fusarium oxysporum sp. albedinis, Alternaria sp, Penicillium expansum, Aspergillus brasiliensis and Rhizopus stolonifer. A quantification of the total polyphenols was mesured out for the aque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
1
0
0
1
Order By: Relevance
“…A study by Amine et al [19] on three aqueous extracts showed that the decocted has a high polyphenol content followed by the infused and after the macerate; which confirms our results. Also, Villalobos-Delgado et al [20] showed in their study that the infusion of Chenopodium ambrosioides contained a high concentration of phenolic compound compared to the ethanolic extract obtained by maceration.…”
Section: Advances In Biological Chemistrysupporting
confidence: 91%
“…A study by Amine et al [19] on three aqueous extracts showed that the decocted has a high polyphenol content followed by the infused and after the macerate; which confirms our results. Also, Villalobos-Delgado et al [20] showed in their study that the infusion of Chenopodium ambrosioides contained a high concentration of phenolic compound compared to the ethanolic extract obtained by maceration.…”
Section: Advances In Biological Chemistrysupporting
confidence: 91%
“…Parmi les potentielles alternatives à ces produits chimiques, les biofongicides à base de plantes peuvent constituer des moyens de lutte contre ces champignons (Jacques, 2013). Ainsi, les travaux de plusieurs auteurs ont mis en évidence des propriétés antifongiques des extraits de certaines plantes locales (Bonzi., 2007 ;Somda et al, 2007 ;Bertrand & Andreu, 2013 ;Kanoun et al, 2014 ;Amine et al, 2017). La présente étude a été initiée dans le but d'évaluer l'efficacité antifongique de l'extrait éthanolique des écorces de Isoberlinia doka sur huit champignons phytopathogènes transmis par les semences.…”
Section: Introductionunclassified